Effects of gamma-secretase inhibitor GSI-34 on bladder cancer cell viability, migration and notch-associated gene expression levels - Roslan, Nadzatul Nabila (2017)
Bladder cancer is a prevalent cancer that is associated with many risk factors including aging and exposure to tobacco. On a molecular level, activating mutations of oncogenes such as Fibroblast Growth Factor Receptor, FGFR3 and the loss-of-function of tumour-suppressor genes such as p53 and pRb have been associated with bladder cancer progression. Previous studies have shown that aberrant Notch signalling has been linked with many cancers including breast cancer, head and neck cancer as well as bladder cancer. Recent genetic studies have shown that Notch receptor mutations are associated with bladder cancer but the mechanism of action of these Notch receptor mutations remains unclear. One of the key enzymes that activates the Notch signalling pathway is gamma-secretase. Thus, gamma-secretase is an attractive drug target. The aim of this study was to determine the effect of a gamma-secretase inhibitor, GSI-34, on bladder cancer cell viability, cell migration and expression levels of Notch receptor genes and Notch downstream targets genes. Using MTT assay, the cytotoxic effect of GSI-34 on the viability of bladder cancer cells was tested. GSI-34 showed a cytotoxic effect against RT112 cells but did not affect the cellular viability of EJ28, SW780 and 5637. Another gamma-secretase inhibitor, DAPT also reduced the RT112 cell viability and minimally supressed 5637 cell viability. The effect of GSI-34 on bladder cancer cell migration was also evaluated using an in vitro migration assay. GSI-34 inhibited SW780 and 5637 cell migrations but enhanced EJ28 cell migration. However, GSI-34 had no effect on RT112 cell migration. Further examination on the effect of GSI-34 on the gene expression levels of Notch receptor genes and Notch downstream target genes was performed using RT-qPCR. Based on the analysis of gene expression, NOTCH2 genes was consistently upregulated in all bladder cancer cells examined. In contrast, HES1 was downregulated in EJ28, SW780 and 5637 cells upon GSI-34 treatment. The DUSP1 gene was also consistently upregulated in all bladder cancer cells. This study identified that RT112 cells are sensitive towards GSI-34 while other cells; EJ28, SW780 and 5637 cells are more resistant towards GSI-34. This study also showed that bladder cancer cells are potentially resistant towards GSI-34 through the downregulation of HES1 and the upregulation of NOTCH2. In addition, higher levels of DUSP1 expression is associated with greater sensitivity towards GSI-34 treatment. The findings from this study identifies GSI-34 as a potential therapeutic target for a subset of bladder cancers. However, the role of NOTCH genes as well as associated genes need to be further understood to ensure effective translation of potential gamma-secretase inhibitors such as GSI-34 as effective bladder cancer therapeutics in the future.